Choosing to run : a memoir - Linden, Des, 1983-; Ford, Bonnie D. (Dutton, 2023)
"An inspirational memoir from Olympian and Boston Marathon winner Des Linden, sharing both her personal story and what motivates her to get up and run every day"--